INDONESIAN ADOLESCENT COPING STRATEGY IN FACING COVID PANDEMIC 19: META ANALYSIS - Lubis, Syawaludin (Psikoislamedia: Jurnal Psikologi, 2020)
The Covid 19 pandemic forced all countries to adopt Social Distancing policies to prevent the spread of the virus. The perceived impact is the change in the dynamics of people's daily lives, where this change from being accustomed to socializing to having to be alone, from interacting to isolating. Teenagers are the most felt part of the impact of this Social Distancing, ranging from school at home, sports at home, gathering at home all activities done at home, this results in the onset of stress due to monotonous and boring activities. Therefore a strategy is needed to overcome the effects of the Covid Pandemic 19. This research method is a literature study, meta-analysis that is analyzing in-depth research journals related to Coping and Covid-19 Pandemic, articles-articles sourced from reputable journal journalists including Scopus including http://link.springer.com, http://seacrh.proquest.com, http://onlinelibrary.wiley.com ,and http://tandfonline.com. The research results show that Coping Strategy is a way for someone to overcome the problems that occur in him, Coping is very adaptive and can be incorporated into the cultural values of each Individual such as the values of spiritual beliefs, thinking patterns and strengths that exist in yourself and the environment. The conclusion is trying to adapt the results of several studies on Coping to deal with Pandemic by combining the cultural potential that exists in Indonesia. This research suggestion is still theoretical, and can be continued in field research